Correlation between nucleation, phase transition and dynamic melt-crystallization kinetics in PAni/PVDF blends1. Issue 91 (9th October 2015) - Biswas, Swarup; Dutta, Bula; Bhattacharya, Subhratanu
<x xml:space="preserve">Abstract</x> The dynamic melt crystallization kinetics of polyaniline (PAni)/poly(vinylidene fluoride) (PVDF) blends of different compositions has been investigated to understand the influence of PAni on the heterogeneous nucleation and phase transition of PVDF.